Pengaruh Pelatihan dan Kompensasi Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening pada Grand Keisha Hotel di Yogyakarta - Hilmi, Adrian Novrizal; Setiawati, Trias (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The aim of this research is to find out whether there is a correlation between training and compensation on employee performance with intervention by the job satisfaction variable using a quantitative methodology where researchers distributed questionnaires to collect information on 66 samples taken from 66 existing populations. The data that has been collected is then analyzed using path analysis and regression methods where the results are found that training and compensation play a positive role in influencing employee performance and job satisfaction. Job satisfaction has a positive influence on employee performance. It was also found that the influence of training on employee performance at the Grand Keisha Hotel Yogyakarta could not be mediated by job satisfaction, but the influence of compensation on employee performance could be mediated by job satisfaction